CUSTOMER ENGAGEMENT AS THE KEY DRIVER OF PURCHASE INTENTION IN SOCIAL MEDIA MARKETING - Imaduddin, Iqbal; Hermadi, Irman; Munandar, Jono M (LPPM Universitas Jambi, 2026)
This study examines the influence of Social Media Marketing Activities (SMMA) dimensions on Purchase Intention through Brand Equity and Customer Engagement among premium smartphone consumers. Therefore, this research aims to analyze the effects of Entertainment, Interaction, Trendiness, Electronic Word-of-Mouth (E-WOM), and Advertising on Brand Equity and Customer Engagement, as well as their implications for Purchase Intention. This study employed a quantitative cross-sectional design using purposive sampling. Data were collected from 175 iPhone users in the Greater Jakarta area through structured online questionnaires measured using a five-point Likert scale. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that Interaction and E-WOM significantly influence both Brand Equity and Customer Engagement, while Entertainment, Trendiness, and Advertising show limited influence on Brand Equity. Furthermore, Customer Engagement demonstrates the strongest direct effect on Purchase Intention, exceeding the influence of Brand Equity. The mediation analysis also confirms that Customer Engagement acts as the dominant mediating variable in the relationship between SMMA and Purchase Intention.The novelty of this study lies in the introduction of the concept of Interactive Community-Based Brand Valuation, which emphasizes that brand value in digital environments is increasingly shaped through consumer interaction and engagement rather than conventional promotional activities. The findings imply that companies should shift their digital marketing strategies from content-oriented promotion toward engagement-driven communication and community interaction to enhance consumer purchase intention in highly competitive digital markets.